PENGARUH PENERAPAN INTERNET BANKING TERHADAP KINERJA PERBANKAN DI INDONESIA - Mardhiyah Dwi Ilhami; Novia Sari Wati Story (Journal Of Institution And Sharia Finance, 2023)
The purpose of this research is to examine the effect of internet banking application to the financial performance of banking which consist of NPL, LDR, ROA, ROE, BOPO and CAR. Study sample consisted of 67 banks in Indonesia from 4 categories with the study period from the first quarter of 2014 to the fourth quarter of 2016. This research used multivariate method and the data test was done by panel data regression analysis with random effect technique. The results showed that the application of internet banking from the risk profile proved to reduce credit risk with a negative effect on NPL variables. However, from the risk of liquidity internet banking application has no effect on LDR variable. While from the ratio of earnings, the results showed the application of internet banking has no effect on ROA, ROE and BOPO variable, and from the capital, the implementation of internet banking is not characterized by an increase in banking capital which means, the implementation of internet banking has no affect on CAR variable.